Textile Aging Characterization on New Generations of Explanted Commercial Endoprostheses: A Preliminary Study. (September 2017) - ,; Albertini, J.-N.; Favre, J.-P.; Duprey, A.; Anidjar, S.; Battelier, J.; Chabert, S.; Chiesa, R.; Corpataux, J.-M.; Deglise, S.; Daligault, M.; Picquet, J.; et al.
Abstract : Objective/background: The goal of the present study was to assess the aging phenomena on second-generation textile endoprostheses (EPs) through explant analysis and to establish a preliminary classification of observed defects and material damages. Methods: From January 2011 to June 2016 110 second- and recent-generation EPs were collected as a part of a European collaborative retrieval program. The analysis focused on the first 41 consecutive commercial EPs collected between 2011 and 2014 and made from polyethylene terephthalate. Explants were submitted to a standardized evaluation protocol, which included data recording, eye-naked evaluation, cleaning of organic remnants, and structural analysis under numerical optical microscopy. Observations were reported using a classification based on 15 features evaluating the fabric, the stitches between the fabric and the stents, and the stents. The total surface area of the holes within the fabric was measured. Results: EPs were implanted for thoracic and abdominal procedures in 12 and 29 cases, respectively. The mean ± SD duration of implantation was 34 ± 26 months (range 2 days–8 years). Sixty-four percent of the samples demonstrated at least one defect caused by compression damage potentially related to the insertion of the EP within the delivery system, which promoted holes and tears. Ninety-five percent of all EPs demonstrated at least one type of abrasion on the stitches. The degradation of the stitches and the number of ruptures increased with duration of implantation. Stent degradation was rare and consisted of corrosion and rupture. Cumulated holed surface area increased with time and was measured up to 13.5 mm 2 . Conclusion: Various aging-related phenomena on commercial textile EPs were identified and classified. Main damaging mechanisms were related to compression and abrasion leading to tears and holes in the fabric and rupture of stitches.